Lesbian Representation In Bengkulu City (Studies In Paired Ra And Ad) - Nadia Amanda Amanda; Anis Endang; Bayu Risdiyanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
He created man in pairs, namely male and female to build a harmonious family. Humans, both male and female, carry out their duties according to the nature given by the creator. In terms of human social life, it is inseparable from the problems of life. One of the problems that usually exist in society is the problem of homosexuality. Society and lesbians separate their existence because society considers the irregularity of sexual desires and the lifestyle of lesbians. A person becomes a lesbian because of the wrong association by lesbians so that this deviation occurs. The purpose of this study was to determine the representation of lesbians in Bengkulu City. This representation is seen from the reality, representation, and ideology related to the background, behavior and views of the lesbians. This study uses a qualitative research method with a case study approach. The results of this study (1) relate to the reality of informants becoming lesbians due to environmental factors, lack of family supervision so that they fall into lesbians. (2) related to the representation that lesbians admit that there are no special symbols that they use. (3) and finally related to the ideology, the informants realized that lesbian is a social deviation, wrong association.